Comparative Evidence on the Topical Wound-Healing Potential of Sap, Stem Bark, and Leaves of Pterocarpus indicus: A Narrative Review - Tessalonika Shinta Ratriani; Astheria Eryani; Ghani Phalosa (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Skin wounds require coordinated control of inflammation, oxidative stress, microbial contamination, and tissue regeneration. Pterocarpus indicus has traditionally been used for inflammatory, infectious, and skin-related conditions, but the relative suitability of its sap, stem bark, and leaves for topical wound-healing development remains unclear. This narrative review comparatively evaluated the phytochemical characteristics, pharmacological activities, direct wound-healing evidence, processing considerations, safety, and sustainability of these three plant parts. Relevant literature was identified through Scopus, PubMed, Web of Science, ScienceDirect, and Google Scholar, with priority given to phytochemical, in vitro, and in vivo studies. The reviewed evidence indicates that sap, stem bark, and leaves are pharmacologically distinct and should not be considered interchangeable materials. Stem bark currently provides the most direct wound-specific evidence through preclinical evaluation of re-epithelialization, although the findings remain preliminary and do not demonstrate superiority over the reference treatment. Leaves are supported mainly by antioxidant and antibacterial activities associated with flavonoids, terpenoids, and other secondary metabolites, whereas direct evidence for wound contraction and histopathological recovery remains insufficient. Sap contains flavonoids and has plausible astringent and antibacterial potential, but its chemical standardization, effective topical dose, dermal safety, formulation stability, and direct effects on tissue regeneration have not been adequately established. Consequently, none of the three plant parts can currently be considered definitively superior. Standardized head-to-head studies using equivalent doses, identical topical vehicles, relevant wound models, and integrated macroscopic, histopathological, microbiological, and safety outcomes are required to determine their comparative therapeutic value and translational feasibility.